A Novel Communication and Radar System for Underground Railway Applications - Lienard, Martine; Degauque, Pierre; Laly, Pierre (European Journal of Transport and Infrastructure Research, 2004)
A system allowing data to be exchanged between two successive trains in a tunnel, while simultaneously measuring the distance between them, would help to optimize train traffic in very long tunnels, without lowering safety standards. A study including both theoretical and experimental phases was conducted to design and optimize such a system and focused on the Channel Tunnel, between France and England, where a minimum range of 5 km is necessary for operational use. A prototype, operating at 2.45 GHz and based on this new concept, produced successful results. Given that this technique would also be useful in any underground rail system, particularly those that are automated, the prototype was also tested on subway lines, in Lille and Paris.